2016
DOI: 10.5350/dajpn2016290404
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the relationship between problematic internet use and parent-adolescent relationship quality, loneliness, anger, and problem solving skills

Abstract: The assessment of the relationship between problematic internet use and parent-adolescent relationship quality, loneliness, anger, and problem solving skillsObjective: The main purpose of this study was to investigate relationships between problematic internet use, and parent-adolescent relationship quality, loneliness, anger, and problem solving skills. Another aim of the current study was to find out differences related to sociodemographic variables, such as gender and socioeconomic status in problematic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…Loneliness is said to be associated with negative mood and destructive behavioral characteristics . Studies show that loneliness is connected to many negative issues such as hopelessness, depression, negative attitude, and ineffective social skills . Loneliness may lead to serious health problems both physically and psychologically .…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is said to be associated with negative mood and destructive behavioral characteristics . Studies show that loneliness is connected to many negative issues such as hopelessness, depression, negative attitude, and ineffective social skills . Loneliness may lead to serious health problems both physically and psychologically .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated gender differences in internet addiction (Bakken et al, 2009, Say andBatıgün Durak, 2016). These studies reported that males were more addicted to the internet compared to females (Şahin, 2011;Tonioni et al, 2012;Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ergenlerin internet kullanım süreleri ise değişiklik göstermektedir (Oktan, 2015;Yüksel & Yılmaz, 2016). Yüksel ve Yılmaz'ın (2016) çalışmasında ergenlerin interneti haftada 22 saat ve üzerinde kullanma oranının yüksek olduğu; bir diğer çalışmada katılımcıların %36.00'sının günde bir saat, %22.00'sinin bir-iki saat internet kullandığı (Kaşıkcı et al, 2014); üniversite öğrencileri ile yapılan çalışmada ise katılımcıların yarıya yakınının günde 3-5 saatini internette geçirdiği bulunmuştur (Dinçer et al, 2014;Say & Durak Batıgün, 2016). Ergenlerin internet kullanım süresinin günde 2-5 saat değişebildiği görülmektedir.…”
Section: Introductionunclassified
“…The study by Yüksel and Yılmaz (2016) found that adolescents used the internet 22 hours and more, while another study found that 36.00% of the participants used the Internet one hour a day and that 22.00% used it one-two hours daily (Kaşıkcı et al, 2014). Another study conducted with university students (Dinçer et al, 2014;Say & Durak Batıgün, 2016) found that almost half of the participants spent 3-5 hours a day on the internet. The internet use of adolescents appears to vary between two and five hours.…”
Section: Introductionmentioning
confidence: 99%